Effect of tandospirone, a serotonin-1A receptor partial agonist, on information processing and locomotion in dizocilpine-treated rats - Bubenikova-Valesova, Vera; Svoboda, Jan; Horacek, Jiri; Sumiyoshi, Tomiki (Psychopharmacology, 2010)
RATIONALE: Augmentation therapy with serotonin-1A receptor (5-HT1A) partial agonists has been suggested to ameliorate psychotic symptoms in patients with schizophrenia. OBJECTIVE AND METHODS: The objective of the present study was to examine the effect of repeated administration of tandospirone (0.05 and 5 mg/kg) on locomotor activity in a novel environment and on sensorimotor gating in rats treated with the N-methyl-D-aspartate receptor antagonist MK-801, which has been used in animal models of schizophrenia. Furthermore, we sought to determine whether the effect of tandospirone on these behavioural measures is blocked by WAY 100635 (0.3 mg/kg), a 5-HT1A receptor antagonist, and whether there is an interaction between haloperidol (0.1 mg/kg; a dopamine-D2 receptor antagonist) and tandospirone. RESULTS: Tandospirone at 5 mg/kg, but not 0.05 mg/kg, decreased locomotor activity in saline or MK-801-treated rats, which were not affected by co-treatment with WAY 100635. Haloperidol decreased locomotion both in saline and MK-801-treated animals, and this effect was not evident in the latter group receiving the higher dose of tandospirone. Tandospirone (5 mg/kg)-induced disruption of sensorimotor gating in saline or MK-801-treated animals was reversed by WAY-100635, but not by haloperidol. CONCLUSIONS: These findings suggest that behavioural changes induced by tandospirone are not fully blocked by 5-HT1A antagonists and that tandospirone (5 mg/kg) potentiates the effect of MK-801. Overall, these findings point to an interaction between NMDA and 5-HT(1A) receptors. Part of the effect of tandospirone on locomotor activity may be mediated by the actions of its active metabolites on other neurotransmitter systems.
Keywords: Animals; Dizocilpine Maleate; vztah mezi dávkou a účinkem léčiva; Receptor, Serotonin, 5-HT1A; pyrimidiny; antipsychotika; Antipsychotic Agents; Rats, Wistar; Excitatory Amino Acid Antagonists; piperaziny; Pyrimidines; pohybová aktivita; haloperidol; receptor serotoninový 5-HT1A; Haloperidol; Isoindoles; schizofrenie; senzorický gating; Serotonin Receptor Agonists; Dose-Response Relationship, Drug; Male; dizocilpinmaleát; modely nemocí na zvířatech; Piperazines; Sensory Gating; Schizophrenia; agonisté serotoninových receptorů; Disease Models, Animal; krysa rodu Rattus; Motor Activity; isoindoly; zvířata; mužské pohlaví; Rats; antagonisté excitačních aminokyselin; potkani Wistar